If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 21 = 9 + -15 Reorder the terms: 21 + 12x = 9 + -15 Combine like terms: 9 + -15 = -6 21 + 12x = -6 Solving 21 + 12x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 12x = -6 + -21 Combine like terms: 21 + -21 = 0 0 + 12x = -6 + -21 12x = -6 + -21 Combine like terms: -6 + -21 = -27 12x = -27 Divide each side by '12'. x = -2.25 Simplifying x = -2.25
| ln(x-2)=8 | | 7x=-5x+20 | | 4x^2+4x=240 | | 6x+3x+x=100 | | 16+13-8b=-13-14b | | t^2-7tx-30x^2= | | 45+4x=-46-3 | | -x+6y=-28 | | -15.02-9.3c-11.98=-4.3c+17.5 | | -5-10p=-10p-3 | | 4x-9=-45 | | y=0x^2-1.3x+7 | | -4x+10y=-28 | | 1n+2n-4n=20 | | 48n^3=147a | | 48n^2=147n | | 2(x+4)+8=2(-x+12) | | 900/675×9 | | 2x/2=36°/2 | | h=16t^2+50t+50 | | 6-2x/3=1-x | | log[3]3x+log[3]4=log[3]36 | | 9v^2-2v-15=0 | | -7x+3(x+5)=-8x-9 | | 3(w+4)-5w=32 | | 30-2x=12+4x | | 3(x-1)+4=25 | | (8x-9)-(7x-9)= | | 5(5p-5)+7p=167 | | C=0.10x+7 | | 56m^2+376m+240=0 | | 6x+30=4x-6 |